Design Of Student Payment Information Using Whatsapp Gateway At AsSalafiyyah Islamic Boarding School Asy-Syafi'iyyah Tambakberas Barat Jombang Based On Website - Setiawan, Deny; Khafidhoh, Nur; Sufaidah, Siti (NEWTON: Networking and Information Technology, 2025)
The development of information technology provides great opportunities to improve administrative efficiency in various fields, including education. As-Salafiyyah Asy-Syafi’iyyah Islamic Boarding School, Tambakberas Barat Jombang faces challenges in managing student tuition payments, which have so far been done manually, making them less effective and prone to late notifications. This study aims to design and develop a website-based student payment information systemintegrated with WhatsApp Gateway to automate payment notifications to student guardians. The method used is Research and Development with the Waterfall model, including needs analysis, design, implementation using PHP and CodeIgniter, and system testing using the Black Box method. The test results show that all the main functions of the system run as expected without significant errors, including student data management, payment posts, bills, and automatic notification delivery via WhatsApp. This system has succeeded in increasing the efficiency and transparency of payment administration and facilitating communication between the Islamic boarding school and student guardians. Thus, the integration of WhatsApp Gateway into the Islamic  school payment information system provides a practical and effective solution tosupport the education process in the digital era.